THE INFLUENCE OF USING PODCAST IN TEACHING SELECTIVE LISTENING OF SMAN 2 KOTA SERANG - Hilmatunisa; Delsa Miranty; Rosmania Rima (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2018)
Listening becomes the first step in learning. Nation and Newton (2012 : 37) states that listening is the natural precursor to speaking; the early stages of language development in a person‘s first language. The objective of the research is to find out the influence of using podcast in teaching listening skill. In order to achieve the objective of this research, the researcher conducted the data through true experimental in quantitative approach. The researcher used cluster random sampling. The researcher took control class and experimental class for gathering the data to be analyzed. Based on the calculation, it was normally distributed and homogen. Based on the result of test of mean difference significant (independent ), it was Calculated or 0.33 2.01. The alternative hypothesis was received. It can be concluded that there was an influence of using podcast in teaching listening at tenth grade of SMAN 2 kota Serang.